Articular cartilage defects of the knee: correlation between magnetic resonance imaging and gross pathology. Issue 9 (September 1990) - Karvonen, R L; Negendank, W G; Fraser, S M; Mayes, M D; An, T; Fernandez-Madrid, F
Abstract : Magnetic resonance imaging (MRI) of the knee articular cartilage is possible owing to the contrast provided by different signal intensities of adjacent menisci and subchondral bone. The objective of this study was to determine the accuracy of MRI in quantitatively detecting thinning and focal defects of articular cartilage in vivo. High resolution MRI was performed followed by dissection of the knee within one hour of amputations above the knee of eight patients (62-89 years) with peripheral vascular disease. Articular cartilage was examined for erosions, surface irregularities, and appearance. Mean thicknesses of femoral and tibial articular cartilage sagittal sections from MRI were statistically indistinguishable from matched gross thicknesses. In those joints in which cartilage erosions, thinning, or irregularities were detected by MRI the same defects were apparent by gross examination. Cartilage that appeared normal by MRI had a normal gross appearance by gross examination. Thus high resolution MRI can accurately predict gross articular cartilage appearance and thickness, allowing an objective, quantitative, noninvasive assessment of eroded cartilage.